Strategies for Managing Emotional Barriers in Students with Autism Through Drum Music Activities: Impacts on Emotional Regulation - Mastoah, Imas; Hasbullah, Hasbullah; Maksum, Ali (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
This study investigates the use of drum music as an effective strategy for managing emotional outbursts in children with Autism Spectrum Disorder (ASD), particularly during tantrums. The research is motivated by parents, teachers, and therapists' challenges in handling tantrum behaviours, which often disrupt the affected child, their peers, and surrounding activities. Drum instruments were introduced as an engaging and enjoyable medium to redirect and regulate such behaviours in children with ASD. This study uses a descriptive qualitative research method to explore drum music's theoretical and practical impacts on emotional regulation. According to the research, children with ASD benefit significantly from playing drum instruments when it comes to emotional regulation. This entertaining and captivating practice promotes emotional self-regulation while acting as a diversion. The study demonstrates how youngsters may naturally and successfully regulate their emotional responses when engaged in drum-playing activities, highlighting the potential of drum music as a therapeutic aid.